A safe treatment option for esophageal bezoars - Yaqub, Sheraz (Elsevier, 2012)
INTRODUCTION: Bezoar in the esophagus is a rare condition and associated with structural or functional abnormalities of the esophagus. Endoscopy is the main tool for diagnosis and treatment for bezoar in the esophagus. PRESENTATION OF CASE: Here we present a case where an endoscopic evacuation of an esophageal bezoar was unsuccessful. We treated the bezoar through a nasogastric tube using a cocktail composed of pancreatic enzymes dissolved in Coca-Cola. DISCUSSION: Endoscopy is regarded as the mainstay for the diagnosis and treatment of esophageal bezoars. However, when this approach fails, other treatment options include dissolution therapy, and surgical exploration and removal of the bezoar. Surgical removal of an esophageal bezoar is associated with a high risk of morbidity and mortality. We advocate that dissolving therapy should be the first choice of treatment when endoscopic evacuation is not possible. CONCLUSION: This is the first report describing a successful treatment of an esophageal bezoar with a cocktail of Coca-Cola and pancreatic enzymes. It is an effective, inexpensive, and worldwide available treatment and should be considered when endoscopic evacuation fails.